Some Recent Advances in Germanium Recovery from Various Resources - Francisco Jose Alguacil; Jose Ignacio Robla (Metals, 2024)
Though nowadays germanium does not reach the range of popularity of other metals, i.e., rare earth elements, its utility in target industries makes it a strategic metal. Though germanium can be found in a series of raw materials, the principal source for its recovery is from secondary wastes of the zinc industry; also, the recyclability of germanium-bearing waste materials is becoming of interest. In this recovery and due to the size of the target materials, because the diffusion and reaction are to be considered, hydrometallurgy performs a key role in achieving this goal. The present work reviews the most recent applications (2023 and 2024 years) of hydrometallurgical operations on the recovery of germanium from different solid and liquid sources.